Stock enhancement of macrobrachium rosenbergii (giant freshwater prawns) inferred by molecular genetics and ecological studies / Mohd Azwan Bin Jaafar - Jaafar, Mohd Azwan (2014)

(untitled)
The freshwater prawn Macrobrachium rosenbergii or locally known as “Udang galah” in Malaysia is ranked as the sixth largest aquaculture species in Asia based on volume. Overharvesting of this species has caused it depletion in all the river line systems in the whole world including Malaysia. A stock enhancement program has been done by the Malaysian Department of Fisheries to fulfil the demand for this prawn. The objective of this study was to determine the productivity success of stock enhancement using 18 microsatellite (Type I and Type II) and mitochondrial DNA markers (mtDNA). In order to evaluate the productivity success, several tests were used to estimate the genetic divergence between the wild samples, the hatchery population, and the tentative recaptured samples. In relation to the stock enhancement program, hatchery juveniles produced in 2007 at Kampung Acheh, Perak were genotyped and then released to natural waters which is Sungai Timun, Negeri Sembilan. Subsequently, recaptured individuals, designated as F1, F2 and F3, were examined using both markers. An analysis of molecular variance (AMOVA) showed that hatchery population and the recaptured individuals had the most minimal differentiation with a value of 0.03 % variation. This result was supported by the UPGMA consensus tree generated using the microsatellites data. On the other hand, mitochondria result also explained that the hatchery population survived and hybridized with the wild type population. This was proven by looking at the haplotypes shared among the populations. Another analysis showed some excess number of alleles, as would be expected from a recent population expansion or from genetic hitchhiking in the wild type population and F1. Pairwise FST showed that the wild type population and the hatchery population were most closely related (0.01964) while the wild type population had a little differentiation with the F2 population. In conclusion, the results showed that the stock enhancement of prawn at Sungai Timun was success but needed to be reassess again to prevent any unexpected outcome such as domestication effect.